2011
DOI: 10.1093/ndt/gfr453
|View full text |Cite
|
Sign up to set email alerts
|

Serum free p-cresyl sulfate levels predict cardiovascular and all-cause mortality in elderly hemodialysis patients--a prospective cohort study

Abstract: Serum free PCS levels may help in predicting risk of all-cause and CV mortality in elderly HD patients beyond traditional and uremia related risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
120
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(124 citation statements)
references
References 30 publications
3
120
1
Order By: Relevance
“…[16][17][18][19] Here, we showed that patients with higher IAA display higher rates of mortality and cardiovascular events. More important, we demonstrated that serum IAA is a significant predictor of cardiovascular events and mortality.…”
Section: Discussionmentioning
confidence: 75%
“…[16][17][18][19] Here, we showed that patients with higher IAA display higher rates of mortality and cardiovascular events. More important, we demonstrated that serum IAA is a significant predictor of cardiovascular events and mortality.…”
Section: Discussionmentioning
confidence: 75%
“…26,27 Recent studies confirmed that free pCS levels were predictive for mortality at different stages of CKD 28 and cardiovascular and all-cause mortality in hemodialysis patients. 29 The relation between pCS and coronary artery disease in patients with no or only moderate degrees of CKD 30 extends the association of this compound with cardiovascular outcomes beyond the scope of pronounced uremia. 31 In clinical studies, it is difficult to determine whether a given uremic toxin intrinsically has deleterious effects or is merely an inert biomarker for the degree of renal dysfunction.…”
Section: Discussionmentioning
confidence: 89%
“…57,58 Both indoxyl sulfate and p-cresyl sulfate per se have repeatedly been related to cardiovascular mortality. [10][11][12][13][14][15][16][17][18][19] Although strategies that more efficiently remove proteinbound solutes, such as frequent dialysis 59 and online hemodiafiltration, 60,61 in controlled studies are associated with improved outcomes, 62,63 it remains difficult to interpret these data because of the presence of confounding factors that affect the outcomes on their own and a lack of selectivity of removal, because dialysis strategies are usually not restricted to protein-bound solutes alone.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 In the past decade, however, a growing number of publications documented the impact of protein-bound uremic toxins on vital processes and an association of their concentration with clinical outcome parameters. 6,[10][11][12][13][14][15][16][17][18][19] One factor blurring the interpretation of the biochemical effects of uremic toxins is the application of unrealistic concentrations compared with the concentrations observed in human CKD in in vitro testing or in vivo animal experiments. 4,20 Moreover, for protein-bound toxins, even with seemingly acceptable total concentrations, the quantities of albumin or protein present are often too low, resulting in unacceptably high and thus, irrelevant free concentrations.…”
mentioning
confidence: 99%